Health risks and outcomes that disproportionately affect women during the Covid-19 pandemic: A review. (December 2020) - Connor, Jade; Madhavan, Sarina; Mokashi, Mugdha; Amanuel, Hanna; Johnson, Natasha R.; Pace, Lydia E.; Bartz, Deborah
Abstract: Background: The Covid-19 pandemic is straining healthcare systems in the US and globally, which has wide-reaching implications for health. Women experience unique health risks and outcomes influenced by their gender, and this narrative review aims to outline how these differences are exacerbated in the Covid-19 pandemic. Observations: It has been well described that men suffer from greater morbidity and mortality once infected with SARS-CoV-2. This review analyzed the health, economic, and social systems that result in gender-based differences in the areas healthcare workforce, reproductive health, drug development, gender-based violence, and mental health during the Covid-19 pandemic. The increased risk of certain negative health outcomes and reduced healthcare access experienced by many women are typically exacerbated during pandemics. We assess data from previous disease outbreaks coupled with literature from the Covid-19 pandemic to examine the impact of gender on women's SARS-CoV-2 exposure and disease risks and overall health status during the Covid-19 pandemic. Conclusions: Gender differences in health risks and implications are likely to be expanded during the Covid-19 pandemic. Efforts to foster equity in health, social, and economic systems during and in the aftermath of Covid-19 may mitigate the inequitable risks posed by pandemics and other times of healthcare stress. Highlights: Female caregivers have an increased exposure risk of contracting SARS-CoV-2. Covid-19 restricts access to family planning and intimate partner violence resources. Multifactorial stress is uniquely exacerbated among women during Covid-19. Gender-informed policies are needed to combat health disparities during pandemics.